On Shamanskii-Like Iterative Method for Solving Fuzzy Nonlinear Equations - Umar Omesa, Audu; Mamat, Mustafa; Mohammed Sulaiman, Ibrahim; Yusuf Waziri, Muhammad; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
This paper proposes a Shamanskii-like method with fixed Jacobian matrix for solving fuzzy nonlinear equation. The method does not require evaluation of the Jacobian at every iteration. This is made possible by considering a fixed Jacobian at 15xn."> . Numerical experimentation are carried out, which shows the superiority of the proposed method against other existing methods.Â Â Â